Finitude and theological anthropology: an interdisciplinary exploration into theological dimensions of finitude - Henriksen, Jan-Olav (Studies in philosophical theology, 2011)
As finite human beings, we are dependent, limited, situated, and vulnerable, and our understanding of ourselves and the world is constantly facing boundaries and restrictions. This book explores how finitude's different dimensions, and its ambiguities, may be understood within the framework of Christian theological anthropology